Optimalisasi Peran Pendamping Desa Dalam Pembangunan dan Pemberdayaan Masyarakat Desa - Agustiar Rivaldi (Perkumpulan Alumni dan Santri Mahyajatul Qurro', 2021)
The presence of Village Facilitators is a demand for Law Number 6 of 2014 concerning Villages and Permendes No. 3 of 2015 concerning Village Assistance. Five years of the village fund and village assistance program have been running, but there are still problems in the field. The purpose of this study was to assess the research to determine the role of village facilitators in the development and empowerment of rural communities. This research is a qualitative study with a field approach. This research is located in villages in Klapanunggal District, Bogor Regency. The author uses data collection techniques in the form of interviews, documentation, and observation. The study results concluded that village facilitators were able to improve the accountability and transparency aspects of village government. Supervision and community participation as the subject and object of development and empowerment over the last five years, in general, have shown their existence towards a change in a healthy and independent village government system. However, the problem of not optimal assistance still occurs both at the central and regional government levels and at the village level.